User-Centered Mobile Navigation: Evaluating Local Usability for Improved UX - Petrova, Sofia; Watanabe, Ken (Journal of Technology Informatics and Engineering, 2025)
Mobile navigation interfaces continue to be plagued by the key usability problem, particularly where widely accepted design traditions fail to address the specific local user population requirements and mental models. This research addresses this significant limitation by using a thorough user-focused measurement framework to search for and investigate context-dependent navigation problems in mobile applications. The research employed a multi-method qualitative approach, using in-depth questionnaires, semi-structured interviews, and laboratory-based usability testing of 15 participants on an interactive Figma prototype that simulated real-world navigation tasks. Our analysis step by step revealed significant navigation issues within the local context, quantified using a 73% task completion rate and a 2.8 participant error average for the core navigation tasks. The most significant usability issues were ambiguous iconography, inconsistent application of platform design patterns, and insufficient system feedback mechanisms. The results conclusively demonstrate that localized usability testing is not merely beneficial but necessary while creating genuinely good and accessible mobile experiences. The study provides a replicable, practical context-aware evaluation approach and tangible, right-now applicable design recommendations, for example, the need to enhance icons with descriptive text labels and use instant visual feedback mechanisms. The study provides developers and designers tangible take-away recommendations for significantly enhancing navigation user experience without trading off methodological availability and implementation convenience in different development environments.